(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
Background One of the signs that a healthy baby is a baby who is experiencing growth according to his age. Growth is more emphasized on increasing physical size, which is becoming bigger or more mature in shape, such as increasing in weight, height, and head circumference. Therefore, newborns need optimal care for future survival. Research Objectives Knowing the Relationship between Age and Parity of Third Trimester Pregnant Women with Knowledge Levels of Newborn Care at at Public Health Center Baamang unit I in 2022. This study uses quantitative methods. Which was carried out at at Public Health Center Baamang unit I in June 2022 with a sample of 31 people using accidental sampling technique from secondary and primary data. Independent variables and dependent variables. Results The factors for the age of pregnant women, namely 20-35 years were 18 people (58%) and the age of pregnant women >35 years was 6 people (19%), parity of primiparous and multiparous pregnant women, each of which included 14 people (45%) and parity of grande multiparous pregnant women is 3 people (10%), the level of knowledge of mothers with sufficient knowledge is 15 people (48%) and the level of knowledge of pregnant women with good knowledge is 4 people (13%), age with knowledge level of pregnant women pregnant women aged 20-35 years with sufficient knowledge as many as 9 people (29%), pregnant women aged> 35 years with good and sufficient knowledge as much as 1 person (3.2 %), parity with knowledge level of primiparous and multiparous pregnant women with less knowledge and 8 people (25.8%), while the minority of primiparous and grande multiparous pregnant women with good knowledge were 1 person (3.2%).